Compliance and Determinants of Spectacle Wear Among Moroccan Adults Residing Beni-Mellal Khénifra Region - Abderrahim Dahbi; Ahmed Chetoui; Farida Bentayeb; Samya Korziti; Abdelilah Errachidi; Youssef El merabet (British and Irish Orthoptic Journal, 2024)
Background and Objective: Ensuring a high level of adherence to wearing spectacles is essential to preserve eye health and achieve optimal vision correction. Comprehending the factors influencing adherence to wearing spectacles can inform strategies to improve eye care outcomes. This study aimed to assess the prevalence and factors influencing adherence to wearing spectacles among Moroccan adults residing the Beni-Mellal Khenifra region. Methods: A cross-sectional interview survey was conducted involving 389 adult spectacle wearers. Participants were recruited through a multilevel random sampling technique and interviewed using a structured questionnaire. This questionnaire collected data on demographics, spectacle prescription, usage patterns, and barriers to compliance. Compliance was assessed based on self-reported frequency and duration of spectacle wear according to the prescription. Possible factors influencing the wearing of spectacles were investigated using both univariate and multivariate regression models. Results: This study revealed that 57.6% of participants adhered to the recommended use of spectacles. Factors associated with compliance were higher education level, longer duration of spectacle use, awareness about the importance of spectacle wear, absence of a family history, specific refractive error types, and increased severity of refractive errors. Participants reported various reasons for not adhering to the recommended use of spectacles, with the most common being forgetfulness, perceiving improved vision without spectacle, discomfort while wearing spectacle, difficulty adapting to spectacle, and loss of spectacle. Conclusion: Given the high prevalence of non-compliance to spectacle wear among adults in the Beni-Mellal Khenifra region, it is evident that additional efforts are required to improve understanding and education regarding the advantages of consistent spectacle usage. Targeted educational and awareness initiatives have the potential to substantially enhance adherence rates and consequently improve visual health outcomes in the region.